Cholesterol pericarditis associated with rheumatoid arthritis: A rare case report. Issue 44 (November 2016) - Qian, Lin-Yan; Pang, Jie; Che, Xian-Da; Ding, Ya-Hui; Zou, Hai; Zhou, Bing
Abstract: Background: Cholesterol pericarditis (CP) is a special type of pericarditis. It is characterized by chronic pericardial effusion with high cholesterol concentration and with or without the formation of crystals in pericardial effusion. Methods: In this case report, we described a 74-year-old male with massive pericardial effusion. He presented with no symptoms. However, he had 8-year history of rheumatoid arthritis medicated with methotrexate, celecoxib, and prednisone, and 5-year history of hypertension medicated with amlodipine besylate. On admission, transthoracic echocardiography revealed a large pericardial effusion. Results: We performed pericardiocentesis for this patient and a lot of cholesterol crystals were found in pericardial effusion under the microscope. A successful operation of thoracoscopic pericardiectomy was proceeded, and the diagnosis was confirmed by surgical pathology. The patient was well recovered and discharged on the tenth day after surgery. It could be predicted that pericardiectomy under video-assisted thoracoscope could be a promising therapy for CP. Conclusion: Rheumatoid arthritis may cause CP with no symptoms. Pericardiectomy could be a promising therapy for CP.